Anthropology of Health: Contributions to the Construction of New Educational Practices - Santos , Adelcio Machado dos (Seven Editora, 2023)
This article intends to analyze in depth the directions on the contributions of health anthropology to the construction of new educational practices in health, addressing the development of this area of knowledge and its contribution to a more conscious practice of health professionals and society as a whole. Therefore, we intend to answer the following question: To what extent can Health Anthropology contribute to the use of health education practices in different cultures, based on the literature review? As a form of research, it was used as a method, the bibliographic research that aims to gather information and data that will serve as a basis for the construction of this article. In this analysis, we seek to conceptualize and contextualize the Anthropology of Health and education, pointing out its social aspects that address society and its various cultures, making a panoramic analysis of the main transformations that the Anthropology of Health has been experiencing in the world, establishing connections between space and its relationship with the environment,  associated with global cultures and science. As a result, it was found that new requests for education were imposed by the significant advances of the productive forces, which came to generate a new culture centered on scientific and technological knowledge, considered today as the most effective factor of production in the capitalist world. In conclusion, it was shown that, in recent times, the opportunities and intrinsic risks in the global exchange of data, information, and knowledge have become a social issue, being in constant movement and renewal. DOI:https://doi.org/10.56238/ptoketheeducati-002